Bank Wakaf Mikro and Creative Economics in Pesantren Buntet - Jehan Maya Zayanie; Ahsana Fitria; Rosidatul Kamariah (Shirkah: Journal of Economics and Business, 2019)
The launch of the Bank Wakaf Mikro (Micro Wakaf Bank/BWM) at the pesantren by the Financial Services Authority (OJK) has received a positive response to realizing economic opportunities in the pesantren. This study aims to examine the role of pesantren in empowering creative economics through the BWM program. This study was conducted by doing in-depth observations and interviews. The researchers gathered data using purposive sampling and snowball sampling techniques. The research findings illustrate the presence of BWM at the pesantren Buntet, Cirebon, West Java, Indonesia has provided a new forum, both for the leaders of the pesantren and the community around the pesantren to carry out their economic potential. Communities surrounding the pesantren argue that BWM has been able to overcome the difficulties in accessing financing needs on a micro-scale. However, the BWM needs to increase the amount of funding and products to follow customers' needs in order to create more promising business variations.Â Keywords: pesantren, OJK, micro bank, Buntet, Cirebon